Conservação in vitro e aclimatização de Epidendroideae (Orchidaceae) do Estado de Sergipe - Menezes, Thays Saynara Alves (2014)
Orchids are considered the oldest among the ornamental species, and are herbaceous and perennial plants of high commercial value. The objective of this work was to develop protocols for in vitro conservation using the slow growth technique, and acclimatization of species of the subfamily Epidendroideae (Orchidaceae) of Sergipe State. The experiments were conducted in the Laboratory of Tissue Culture and Plant Breeding, Department of Agronomic Engineering, Federal University of Sergipe. We conducted two conservation experiments, both in a completely randomized design, the first in a 4x3x2 factorial scheme, testing four concentrations of salts of MS medium (100%, 75%, 50%, 25% salts), three species (Catasetum macrocarpum, Oeceoclades maculata and Polystachya estrellensis) and two temperatures (18 and 25ºC), and the second in a 3x3x2 factorial scheme, testing three combinations of carbon sources and osmotic regulators (20 g.L-1 sucrose, 10 g.L-1 sucrose + 5 g.L-1 mannitol, 10 g.L-1 sucrose + 5 g.L-1 sorbitol), three species (C. macrocarpum, O. maculata and P. estrellensis) and two temperatures (18 and 25ºC). For acclimatization, the experiment also was conducted in a completely randomized design, testing eight substrates [sand and earthworm castings (4:1); sand, coconut coir and earthworm castings (2:2:1); sand, crushed pine bark and earthworm castings (2:2:1); sand, crushed pine bark, coconut coir and earthworm castings (2:1:1:1); sand; sand and coconut coir (1:1); sand and crushed pine bark (1:1); sand, crushed pine bark and coconut coir (2:1:1)] and two species (O. macrocarpum and C. maculata). For in vitro conservation of C. macrocarpum, O. maculata and P. estrellensis for a period of 450 days, we should use culture medium containing 25% of MS salts at a temperature of 25°C or 20 g.L-1 of sucrose at 25°C. Acclimatization of micropropagated seedlings of C. macrocarpum can be performed using sand, crushed pine bark and earthworm castings (2:2:1) as the substrate, and for O. maculata we recommend to use only sand.